Integrasi Nilai-Nilai Islam dalam Pembelajaran Matematika di Madrasah Ibtidaiyyah - Ilma, Fatkhul; Irawan, Wahyu Henky; Abdussakir, Abdussakir (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this research is to find out the integration of Islamic values in mathematics learning at Madrasah Ibtidaiyyah. This study uses a library research method or library research, literature study is a research method that utilizes library sources as a source in research activities. The data collection technique used in this literature research is to look for data on matters or variables in the form of notes, books, papers, or articles and journals. After the data is collected, content analysis is carried out to get the right and accurate conclusion formulation. Data analysis consists of data reduction, data presentation, and conclusion drawing. The results of this study found several discussions regarding the Definition of Integration of Islamic Values, Mathematics Learning, Principles of Knowledge Integration, Strategies for the Integration of Islamic Values in Mathematics Learning, and Integration of Islamic Values in Mathematics Learning. The conclusion of this study is that the integration of Islamic values in the mathematics learning process at Madrasah Ibtidaiyah initially felt difficult to implement. Especially for mathematics subjects that have a lot to do with numbers, formulas, and geometric construction, it will feel easy to apply if we as educators always try to find gaps to instill Islamic religious values in classroom learning